The Urgency of Judge's Legal Reasoning in Deciding on an Environmental Crime Case Based on an Ecocentric Approach (Review of Case Decision No. 640/PID.B/LH/2021/PT PBR) - Ainun Jiwanti; Eko Soponyono (Jurnal Jurisprudence, 2022)
Objective: This study aims to analyze how the legal reasoning of the Pekanbaru High Court Judge in Decision No. 640/PID.B/LH/2021/PT PBR, and at the same time reviewing decisions at the previous level and show how important the judge's legal reasoning is based on an ecocentric approach in deciding environmental crime cases. Methods: This type of research is a normative law using statutory, case, and conceptual approaches. Findings: The panel of judges of the Pekanbaru High Court granted the defendant's appeal, PT. Gandaerah Hendana because Article 98 paragraph (1) of the PPLH (Environmental Protection and Management) Law that the public prosecutor indicted is a material offense that must be linked to its formal elements (Article 108 of the PPLH Law). It differs from the opinion of the Rengat District Court panel of judges, which stated that because the meaning of "action" in Article 98 paragraph (1) of the PPLH Law is so broad, the action can be in any form as long as the consequences stipulated in the formulation of the offense occurred. The action in question does not only do prohibited things but also includes not carrying out legal obligations (omission offenses). Since the burned land is the defendant's right to cultivate area, PT. Gandaerah Hendana, the process of extinguishing the fire on the land is the responsibility of the defendant, PT. Gandaerah Hendana. In this regard, the ecocentric approach in judges’ legal reasoning is urgent because, so far, the positivistic-formal and anthropocentric approaches have made judges only oriented to human interests. With an ecocentric approach, judges will pay attention to environmental sustainability when deciding the case being examined so that judges will produce outputs in the form of pro-environmentally oriented decisions. Benefits: The results of this study are expected to enrich references for academics and become input for law enforcers, especially judges, about the importance of legal reasoning based on an ecocentric approach in deciding environmental crime cases. Novelty: The discussion in this study will provide a perspective and explanation of how an ecocentric approach as the basis for legal reasoning for judges can create decisions and enforce environmental laws oriented towards the environment.